Faktor-Faktor yang Mempengaruhi Pychological Well Being pada Mahasiswa di Indonesia: A Systematic Scoping Review - Meininda Rhivent Norhidayah; Elza Kusumawati; Amherstia Pasca Rina (Observasi : Jurnal Publikasi Ilmu Psikologi, 2025)
Objective: This scoping literature review is intended to identify factors that influence Psychological well-being and see the gap synthesis of previous studies. Introduction: Students as the next generation of the nation often face various challenges, both in academic, social, and personal fields. These challenges can affect their psychological well-being, which is an important aspect in supporting the success of studies and life as a whole. Methods and analysis: This study uses 5 main stages, namely the stage of identifying questions, identifying relevant studies, selecting study results, data extraction, data synthesis. Specifically using the PCC framework and paying attention to inclusion and exclusion criteria so that the final results are obtained. Results: The results found from the data selection found a total of 8,401 articles from 1 database and duplication was done twice (in the first check using Rayyan.ai the second work during data selection with Rayyan.ai n = 807 After duplication of data selection based on inclusion exclusion criteria, 63 relevant articles were found. After manual re-detection, the final results were 13 articles that were most relevant to the research topic.